Grouper RIP2 inhibits Singapore grouper iridovirus infection by modulating ASC-caspase-1 interaction - Zhang, Xin; Wu, Siting; Liu, Zetian; Chen, Hong; Liao, Jiaming; Wei, Jingguang; Qin, Qiwei (Frontiers in Immunology, 2023)
Receptor interacting protein 2 (RIP2), serves as a vital sensor of cell stress, is able to respond to cell survival or inflammation, and is involved in antiviral pathways. The clone and characterization of a RIP2 homolog from orange-spotted grouper (Epinephelus coioides) (EcRIP2) were performed for addressing the roles of fish RIP2 in singapore grouper iridovirus (SGIV) infection. Encoded a 602 amino acid protein, EcRIP2 contained two structural domains: S-TKc and CARD. Subcellular localization signified that EcRIP2 existed in cytoplasmic filaments and dot aggregation patterns. After SGIV infection, the EcRIP2 filaments aggregated into larger clusters near the nucleus. The infection of SGIV could notably up-regulate the transcription level of the EcRIP2 gene compared with lipopolysaccharide (LPS) and red grouper nerve necrosis virus (RGNNV). Overexpression of EcRIP2 impeded SGIV replication. The elevated expression levels of inflammatory cytokines induced by SGIV were remarkably hindered by EcRIP2 treatmen. In contrast, EcASC treatment could up-regulate SGIV-induced cytokine expression in the presence of EcCaspase-1. Enhancing amounts of EcRIP2 could overcome the down regulatory effect of EcASC on NF-κB. Nevertheless, increasing doses of EcASC failed to restrain the NF-κB activation in the existence of EcRIP2. Subsequently, it was validated by a co-immunoprecipitation assay that EcRIP2 competed with EcASC binding to EcCaspase-1. With increasing time to SGIV infection, EcCaspase-1 gradually combined with more EcRIP2 than EcASC. Collectively, this paper highlighted that EcRIP2 may impede SGIV-induced hyperinflammation by competing with EcASC for binding EcCaspase-1, thereby suppressing viral replication of SGIV. Our work supplies novel viewpoints into the modulatory mechanism of RIP2-associated pathway and offers a novel view of RIP2-mediated fish diseases.